New Predictive Models for Blood—Brain Barrier Permeability of Drug-like Molecules - Kortagere, Sandhya (2008)
PURPOSE: The goals of the present study were to apply a generalized regression model and support vector machine (SVM) models with Shape Signatures descriptors, to the domain of blood—brain barrier (BBB) modeling. MATERIALS AND METHODS: The Shape Signatures method is a novel computational tool that was used to generate molecular descriptors utilized with the SVM classification technique with various BBB datasets. For comparison purposes we have created a generalized linear regression model with eight MOE descriptors and these same descriptors were also used to create SVM models. RESULTS: The generalized regression model was tested on 100 molecules not in the model and resulted in a correlation r(2)=0.65. SVM models with MOE descriptors were superior to regression models, while Shape Signatures SVM models were comparable or better than those with MOE descriptors. The best 2D shape signature models had 10-fold cross validation prediction accuracy between 80–83% and leave-20%-out testing prediction accuracy between 80–82% as well as correctly predicting 84% of BBB+ compounds (n=95) in an external database of drugs. CONCLUSIONS: Our data indicate that Shape Signatures descriptors can be used with SVM and these models may have utility for predicting blood—brain barrier permeation in drug discovery.